A Numerical Investigation of Flow Characteristics in a Cryogenic Perforated Plate Flowmeter for Vertical Pipe Applications - Yihan Tian; Zhijian Zhang; Zhaozhao Gao; Chen Cui; Liubiao Chen; Junjie Wang (Energies)
To address the research gap regarding the flow characteristics of cryogenic perforated plate flowmeters in vertical pipes and to enhance measurement reliability in challenging environments, this study investigates the flow characteristics of liquid hydrogen in a vertical pipe using a perforated plate flowmeter. Numerical simulations are performed based on an extended derivation of performance parameter formulas in the vertical direction. Various inlet Reynolds numbers, plate thicknesses, and equivalent diameter ratios are analyzed to assess their effects on key performance parameters, including the discharge coefficient, pressure loss coefficient, and stable region. The results indicate that the influence of flow direction on the performance parameters decreases with increasing Reynolds number. Downward flow is associated with smaller discharge coefficients, lower pressure loss coefficients, and reduced upper limits of Reynolds numbers in the stable region. Furthermore, the effects of gravity become more pronounced at larger thicknesses and greater equivalent diameter ratios.